The Influence of Social Capital, Collaborative Competence and Entrepreneurial Behavior to Sustainable Competitive Advantage - Widiyati, Dian; Hasanah, Neneng (AGUSPATI Research Institute, 2022)
The purpose of this study is to analyze the influence of social capital, collaborative competence and collaborative competence on sustainable competitive advantage. The Industrial Revolution 4.0 fundamentally resulted in a change in the way people think, live, and relate to one another. This era will disrupt various human activities in various fields, not only in the field of technology, but also other fields such as economic, social, and political. Industry 4.0 creates new industrial design principles such as simulation models, decentralized decision making, real-time ability to collect and analyze data, provide insights, adapt flexibility to change by reconfiguring individuals and improving service orientation. In a highly dynamic environment, companies need experience and are able to adapt to create a sustainable competitive advantage. This type of research is quantitative research using primary data. The data was obtained by spreading questionnaire questions directly to the public through Google forms. Respondents are micro small and medium enterprises in South Tangerang. The type of questionnaire used is a closed questionnaire. The sample selection procedure is carried out by convenience sampling technique. The study sample amounted to 52 respondents of MSME actors in South Tangerang. The analysis method used is multiple analysis with data processing using Smart-PLS applications. The results showed that social capital and collaborative competence variables had no effect on sustainable competitive advantage, while entrepreneurial behavior variables had an effect on sustainable competitive advantage.